(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
Creatine is synthesized primarily in the liver as a result of methylation of glycocyamine (guanidinoacetate synthesized in the kidneys from the amino acids arginine and glycine) with S-adenosylmethionine. It is then transported through the blood to other organs, muscles and the brain, where it is converted by phosphorylation into the high-energy compound phosphocreatine